Servant Leadership Model in Educational Design - Subekti, Ita; Hariyati, Nunuk; Hendratno, Hendratno (Papanda Publisher, 2025)
This study examines the application of the servant leadership model in educational settings and its impact on school quality, teacher performance, and organizational culture. A systematic literature review was conducted, analyzing 15 articles selected from an initial pool of 201 studies using the PRISMA approach to ensure validity and relevance. The analysis reveals that servant leadership has a significant role in creating a supportive educational environment, enhancing teacher motivation, and strengthening organizational commitment. However, challenges in implementation persist, primarily due to limited understanding and insufficient training among educational leaders. To address these challenges, the study recommends the development of targeted training programs and mentorship initiatives for school principals to promote effective servant leadership practices. This review emphasizes the importance of incorporating servant leadership principles into leadership development programs to enhance their impact on educational outcomes. The paper cites 15 references but does not include tables, graphs, or supplementary appendices. Future research is recommended to explore practical models of servant leadership training in various educational contexts, aiming to support sustainable school improvement.